Research on the Air Filters' Maintenance for Diesel Engines. (2016) - Toma, Marius; Fileru, Iordan
Abstract: The wear of internal combustion engines is strongly influenced by dust particles from the atmosphere by that pass through air filter and reach inside the kinematic couplings of the engine. Air filters have relatively low initial efficiency. As they are used, air filters are impregnated with a layer of fine dust and their filtering efficiency is increasing. This paper aims to investigate the technical state of air filters that equip Renault K9K engine that are being replaced during the preventive maintenance schedule according to manufacturer recommendation. The study refers to the measurement in laboratory conditions on a specialized rig of the restriction generated by the air filter housing, as well as the restriction generated by new and used air filters. The used filters were collected from vehicles that came to service stations for air filters replacement as part of the preventive maintenance schedule. The results are used to establish to what extent the air filters replaced during planned maintenance could still be used, if they were replaced too late or at the appropriate time.